Relationships for vitamin D with childhood height growth velocity and low bone mineral density risk - Xiao, Pei; Cheng, Hong; Wang, Liange; Hou, Dongqing; Li, Haibo; Zhao, Xiaoyuan; Xie, Xianghui; Mi, Jie (Frontiers in Nutrition, 2023)
Objective To investigate how serum 25-hydroxyvitamin D (25[OH]D) affects height growth velocity and the risk of low bone mineral density (BMD) in children. Design A population-based prospective cohort study. Patients and methods A total of 10 450 participants with complete follow-up records from a cohort were included in the current study. Serum 25(OH)D concentrations were measured at baseline and 2-year follow-up, and the average of 2-time measurements was used for analysis. Low BMD was defined as calcaneus speed of sound Z-score ≤ −1. The associations of vitamin D with height growth velocity and the risks of incident low BMD were evaluated using adjusted β and risk ratio (RR). Results After multivariable adjustment, an inverse L-shaped association between serum 25(OH)D concentrations and height growth velocity was observed, leveling off up to 40–60 nmol/L. Overall, each 10 nmol/L higher serum 25(OH)D concentration was associated with a 0.15 cm/year higher height growth velocity (P < 0.001) and a 7% decreased risk of low BMD [RR (95%CI): 0.93 (0.87 0.98)]. Compared to those with vitamin D deficiency, participants who had sufficient vitamin D had a 22% lower risk for low BMD [RR(95%CI): 0.78 (0.62 0.98)]. However, no significant associations between vitamin D and the risk of low BMD were found in overweight and obese children. Conclusion These findings highlight the importance of maintenance of sufficient 25(OH)D concentrations and healthy body weight during childhood in height growth and bone health promotion.